2022
DOI: 10.3390/cancers14194632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of the Eighth Edition Oral Cancer Staging System

Abstract: Objectives: The most notable changes in the eighth edition of the AJCC Cancer Staging System include incorporating the depth of invasion (DOI) into T staging and extranodal extension (ENE) into N staging. In this study, we retrospectively assessed the prognostic and clinical implications of the eighth TNM staging system. Materials and Methods: Patients with Oral Squamous Cell Carcinoma (OSCC) who were treated surgically between 2010 and 2017 were retrospectively reviewed. Tumors were first staged according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(45 reference statements)
2
10
0
Order By: Relevance
“…We speculate that the more extensive, more representative tissue sampling afforded by surgical excision increases the likelihood of detecting foci of microinvasive disease, which may have otherwise been missed with incision. Lower oncologic staging is the most powerful prognosticator in oral cavity cancer, and significantly improved survival outcomes associated with stage I and II disease compared to stage III and IV are well known and supported by our results 1,53–55 . Cox univariate analyses showed significant associations between management of OED by surgical excision of the preceding OED and overall survival, which we speculate is secondary to the significantly lower oncologic staging within the excisional group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We speculate that the more extensive, more representative tissue sampling afforded by surgical excision increases the likelihood of detecting foci of microinvasive disease, which may have otherwise been missed with incision. Lower oncologic staging is the most powerful prognosticator in oral cavity cancer, and significantly improved survival outcomes associated with stage I and II disease compared to stage III and IV are well known and supported by our results 1,53–55 . Cox univariate analyses showed significant associations between management of OED by surgical excision of the preceding OED and overall survival, which we speculate is secondary to the significantly lower oncologic staging within the excisional group.…”
Section: Discussionsupporting
confidence: 83%
“…Lower oncologic staging is the most powerful prognosticator in oral cavity cancer, and significantly improved survival outcomes associated with stage I and II disease compared to stage III and IV are well known and supported by our results. 1,[53][54][55] Cox univariate analyses showed significant associations between management of OED by surgical excision of the preceding OED and overall survival, which we speculate is secondary to the significantly lower oncologic staging within the excisional group. OED with a homogenous clinical appearance was also associated with improved overall survival, which we speculate is explained by the increased likelihood that homogenous OED will be managed by surgical excision supported by logistic regression.…”
Section: Discussionmentioning
confidence: 82%
“…Despite this limitation, we believe that the follow-up period of the patients was longer than that in previous studies. 19,20 Therefore, the cohort was classified according to the 7th edition, which does not consider pathological findings, such as the DOI of the primary tumor or tumor ECS in cervical lymph node metastasis. Although previous studies failed to find a direct relationship between the DOI and prognosis, they found a strong correlation between the DOI and the risk of nodal metastasis, especially in early stage tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective study included 111 OSCC patients’ data retrieved from patient records in the Dental Information Archival Software (DIAS) used in Saveetha Dental College and Hospitals, Saveetha Institute of Medical and Technical Sciences (SIMATS), Chennai, between March 2020 and September 2023 with a purposive sampling technique and ethical approval (IHEC/SDC/UG-1871/23/OMR/332) obtained from the same institute to conduct the study and extract the data. Clinicopathological information of each case, such as age (categorized into seven groups: 21-30 years, 31-40 years, 41-50 years, 51-60 years, 61-70 years, 71-80 years, and 81-90 years), gender, habit duration, anatomical region (buccal mucosa, tongue, maxillary alveolus, mandibular alveolus, combination of maxillary and mandibular alveolus, and floor of the mouth), TNM (tumor, nodal, and metastasis) staging 8th edition, 2017 at the time of diagnosis [ 12 ], perineural invasion, lymphovascular invasion, and overall oral health were assessed with a modified Oral Health Impact Profile (OHIP) questionnaire comprising of seven questions on difficulty in swallowing, taste, mastication, speech, and pain or discomfort in the oral cavity of the patient that were categorized under five domains [ 13 ]. The questions were asked by the physician to the patient postoperatively, and the scores were recorded based on the responses obtained from the patient, which ranged between 0 and 10, to evaluate the oral health-related quality of life.…”
Section: Methodsmentioning
confidence: 99%